Early Pharmacotherapy with Fluoxetine Rescues Dendritic Pathology in the Ts65Dn Mouse Model of Down Syndrome. (3rd September 2012) - Guidi, Sandra; Stagni, Fiorenza; Bianchi, Patrizia; Ciani, Elisabetta; Ragazzi, Elena; Trazzi, Stefania; Grossi, Gabriele; Mangano, Chiara; Calzà, Laura; Bartesaghi, Renata
Abstract Down syndrome DS is a genetic pathology characterized by brain hypotrophy and severe cognitive impairment. Although defective neurogenesis is an important determinant of mental disability, a severe dendritic pathology appears to be an equally important factor. A previous study showed that fluoxetine, a selective serotonin reuptake inhibitor, fully restores neurogenesis in the Ts65Dn mouse model of DS. The goal of the current study was to establish whether fluoxetine also restores dendritic development. In mice aged 45 days, treated with fluoxetine in the postnatal period P3–P15, we examined the dendritic arbor of the granule cells of the dentate gyrus (DG). The granule cells of trisomic mice had a severely hypotrophic dendritic arbor, fewer spines and a reduced innervation than euploid mice. Treatment with fluoxetine fully restored all these defects. In Ts65Dn mice, we found reduced levels of serotonin that were restored by treatment. Results show that a pharmacotherapy with fluoxetine is able to rescue not only the number of granule neurons but also their "quality" in terms of correct maturation and connectivity. These findings strongly suggest that fluoxetine may be a drug of choice for the improvement of the major defects in the DS brain and, possibly, of mental retardation.